(untitled) (Revista horizonte, 2016)
This literature review arises to know what the current perspective regarding the optimal treatment is on insulin resistance (IR), which is defined as a suboptimal reaction to this hormone, and prediabetes (preDT2) defined as impaired blood glucose level, known as the previous step for type 2 Diabetes Mellitus (T2DM) .Physical activity with the most widely used and studied drug of the market - Metformin- were compared. Data bases of similar items were checked in order to collect, summarize and present treatment options and results that different work groups have had; therefore, to know the best working and planning strategy and for this type of patients. As a result, changing lifestyles - mainly physical activity for over 150 minutes per week presents good results by reducing the transition from preDT2 to DT2, if it were exclusively compared to metformin. Exercising also reduces body weight, which is associated with a decrease of transition from preDT2 to DT2. On the other hand, combining both therapies, metformin and exercising, do not get statistically significant achievements if compared to single exercising. In addition, it is described that the use of metformin in prediabetic patients results in a statistically significant reduction over the oxygen consumption, maximum heart rate and duration of exercise.